(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The primary role of traffic control procedures is to protect the network so that it can achieve the required network performance objectives and yield a high quality of service (QoS). To guarantee the QoS, the network implements traffic control using the parameters agreed upon at the start of data transfer, thus avoiding problems with degraded QoS before they occur. This paper presents an efficient model for policing cells transmitted over ATM networks. The model was simulated by a program written in Java. From several simulation test runs and subsequent analysis, it can be deduced that the model gives a minimal cell transfer rate at a minimum intercell period, while the cell delay variation tolerance is held constant. Optimal cell loss ratio is also achieved when the minimum intercell period is held constant and the cell delay variation tolerance is high. The results show minimal cell loss ratio has been achieved and the data throughput of the model is high.